Auditory cues in table tennis: evaluating their effectiveness compared to visual information - Lin, L.-Y.; Liu, Y.-T. (Psychology of Sport and Exercise, 2025)
In table tennis, the sounds of ball-racket impacts provide meaningful cues for identifying the rotational features of the ball, but the contribution of environmental auditory information to table tennis striking performance is still unclear. This exploratory study investigated the role of auditory information as cues for table tennis striking. Eleven elite varsity table tennis players performed forehand push and topspin-drive strokes to return oncoming balls under three information conditions: normal, visual-only with earmuffs and white noise, and auditory-only with goggles occluding vision. The time intervals between impact sounds were analyzed between the two types of oncoming balls. The percentage of successful trials, the in-bounds rate, the kinematics performance of the racket and the ball and movement time lags were analyzed between conditions for push and topspin-drive strokes, respectively. The participants could pick up the distinguishable cues through auditory perception, enabling them to perform push and topspin-drive techniques correctly in the auditory-only condition. However, participants initiated movements later, reduced movement times and distances, and exhibited higher variability of movement time lags when only relying on auditory information. Deprivation of auditory information affected the speed of the racket and the ball at the termination of movement. The elite players could identify the spatial outcome of the oncoming ball by detecting auditory cues. Eliminating their auditory information affected their perception-action coupling, although this information did not play a dominant role in striking.